Employing multimodal dialogic feedback on EFL tertiary students’ writing: Formative assessment framework - Thamrin, Nur Sehang; Madya, Suwarsih; Putro, Nur Hidayanto Pancoro Setyo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Feedback is essential for improving EFL students' writing skills, even though it is still underutilized. Yet, only some studies examine multimodal dialogic feedback (MDF) on students' writing. To address the gap, this study, which employed an exploratory mixed-method, investigated the impact of MDF mediated by utilizing Google Docs and Zoom conferences as convenience platforms in a writing class among some Indonesian university learners and the impact of this MDF on the revision quality of the student texts. Furthermore, the study explored the students' perceptions of MDF from the formative assessment framework. While the quantitative method through classroom action research (CAR) with 39 students recruited purposively, examined the impact of MDF on students' writing skills, the qualitative approach using semi-structured in-person interviews with eleven students recruited conveniently, addressed the student's perceptions of the influence of MDF on their writing skills. The quantitative data were analyzed through simple descriptive statistical analyses to visualize the trend of students' improvement and the instructor's feedback. The qualitative data on the students' positive perceptions of the impact of MDF on their writing were analyzed using thematic analysis. Statistical analyses of the student's texts reveal that the student's writing skills are gradually developing. The results demonstrate how mediating MDF during teaching-learning writing affected the student's work on organization, content, language use, mechanics, and text length. Implications for writing instruction and the instructor's feedback are also discussed. Although this current study has limitations, suggestions for further research are offered.